PERAN PERSEPSI PENGGUNA DALAM MEMEDIASI ADOPSI ARTIFICIAL INTELLIGENCE (AI) DI KALANGAN MAHASISWA AKUNTANSI - Nurabiah, Nurabiah; Pusparini, Herlina; Bambang; Fitriyah, Nur (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2025)
The aim of this study is to analyze the influence of readiness and knowledge on the adoption of Artificial Intelligence (AI), as well as the mediating role of user perceptions on this influence. The Technology Acceptance Model (TAM) theory, which is a popular model for predicting people's attitudes when they decide whether or not to embrace a technology system, is used in this study. The sampling strategy employs a random sampling technique, in which the sample is selected at random to create an unrepresentative skew of the entire population. There were 439 responders in all, and the sample consisted of D3, D4, and S1 accounting students from the city of Mataram. A questionnaire is used to collect data. The clever PLS 3.0 application was utilized to apply the Partial Least Square (PLS) technique in order to evaluate the hypothesis. His research's findings demonstrate that knowledge and readiness have a favorable impact on AI adoption, that knowledge and readiness have a positive impact on AI user perceptions, and that user views can mediate the relationship between knowledge and readiness and AI adoption. This study aids in recognizing patterns in how AI is perceived in accounting settings and helps comprehend and predict how these technological advancements will affect students' capacity to adapt.